TINDAK TUTUR EKSPRESIF PADA KOLOM KOMENTAR YOUTUBE ROCKY GERUNG “GUBERNUR NTT BIKIN HEBOH, PERINTAHKAN SISWA SMA MASUK JAM 5 PAGI. SALAH PAHAM DUNIA PENDIDIKAN” - Nabilah Syafendra; Fatmawati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The tendency of someone to express expressive speech on social media is the background in this study. Many users express themselves by commenting on someone's account video uploads. The purpose of this study was to find out and understand the forms of expressive speech acts in the Rocky Gerung Youtube comments column entitled “The Governor of NTT Makes a Scene, Orders High School Students to Enter at 5 in the Morning. Misunderstanding of the World of Education”. The theory of expressive speech acts in this study is the combined theory of Searle, Nadar, Leech, and Tarigan. The approach in this research is a qualitative approach with content analysis method. The source of the data in this study is a comment on Rocky Gerung's Youtube "The Governor of NTT Makes a Thrill, Orders High School Students to Enter at 5 in the Morning. Misunderstanding of the World of Education”. The data used are expressive speech acts contained in the comments. Data collection techniques used are observing, documenting, and taking notes. The collected data were then analyzed using the Burhan Bungin analysis technique. Based on the results of the study, 156 utterances were found which were identified as expressive speech acts. The most frequent speech acts were expressive speech acts of blaming because the policies set were contradictory so that people expressed their psychological attitudes in the form of blaming comments, while the speech acts that were not found from the results of the analysis were expressive speech acts of interrupting, welcoming, forgiving, condolences, and accusing. The analysis also found new data findings, namely: contempt, support, expressions of disappointment, surprise, and sadness, as well as found several non-literal speech acts with the utterances spoken.